The The Analysis of Influence of Performance Management Policy to Employees Satisfaction in KPP Madya Jakarta Barat - Agnes Anita Carolina; Deddy Supriady Bratakusumah; Maya Puspita Dewi (Universitas Pendidikan Ganesha, 2024)
This study aims to create employee performance in accordance with the bureaucratic reform plan, increase human resources, and productivity at the West Jakarta Madya Tax Service Office (KPP). The subjects of this study include the Head of Supervision Section, Functional Examiner, Extension Functional Officer, and Account Representative. The informant sample was taken using the purposive sampling method, involving 7 participants representing various positions in KPP Madya West Jakarta. The collected data were analyzed qualitatively descriptively. The results showed that independent variables which include policy clarity systems, human resources, leadership, motivation, and job satisfaction had a significant influence on employee performance at KPP Madya West Jakarta. In addition, forced ratings and distributions also affect employee job satisfaction, as well as the amount of performance allowances received. These findings provide an understanding of the complex relationship between the rating system, human resources, leadership, motivation, and job satisfaction in KPP Madya West Jakarta. This research has important implications in the development of effective strategies to improve employee performance through a measurable, objective, accountable, and transparent rating system.